Stomatal closure during water deficit is controlled by below-ground hydraulics - Abdalla, Mohanned; Ahmed, Mutez Ali; Cai, Gaochao; Wankmüller, Fabian; Schwartz, Nimrod; Litig, Or; Javaux, Mathieu; Carminati, Andrea (Annals of botany, 2022)
Stomatal closure allows plants to promptly respond to water shortage. Although the coordination between stomatal regulation, leaf and xylem hydraulics has been extensively investigated, the impact of below-ground hydraulics on stomatal regulation remains unknown. We used a novel root pressure chamber to measure, during soil drying, the relation between transpiration rate (E) and leaf xylem water pressure (ψleaf-x) in tomato shoots grafted onto two contrasting rootstocks, a long and a short one. In parallel, we also measured the E(ψleaf-x) relation without pressurization. A soil-plant hydraulic model was used to reproduce the measurements. We hypothesize that (1) stomata close when the E(ψleaf-x) relation becomes non-linear and (2) non-linearity occurs at higher soil water contents and lower transpiration rates in short-rooted plants. The E(ψleaf-x) relation was linear in wet conditions and became non-linear as the soil dried. Changing below-ground traits (i.e. root system) significantly affected the E(ψleaf-x) relation during soil drying. Plants with shorter root systems required larger gradients in soil water pressure to sustain the same transpiration rate and exhibited an earlier non-linearity and stomatal closure. We conclude that, during soil drying, stomatal regulation is controlled by below-ground hydraulics in a predictable way. The model suggests that the loss of hydraulic conductivity occurred in soil. These results prove that stomatal regulation is intimately tied to root and soil hydraulic conductances.